Hubungan Pemberian Edukasi Kesehatan Reproduksi dan Kesehatan Ibu dan Anak Dengan Pengetahuan Kader Kesehatan di Kelurahan Tugu - Hanifah, Laily; Izzah, Raudina; Maryusman, Taufik; Amar, M. Ikhsan (Universitas Hang Tuah Pekanbaru, 2026)
Maternal and Child Health is one of the indicators that determines the level of public health in a country. Discussions surrounding reproductive health and maternal and child health are closely related to the daily lives of community health cadres, who often interact with mothers and families. This study conducted in 2022 aims to determine differences in cadres’ knowledge of reproductive health and maternal and child health before and after counseling was conducted in Depok. There were respondents in this study, using a one-group pre-test–post-test design, with univariate analysis and bivariate analysis using the Wilcoxon test. The majority of respondents (86.60%) were adults, and 76.64% of them had a secondary level of education. After the intervention, there was an increase in knowledge of 69.37%. The results of the Wilcoxon test showed a p-value of 0.000 (< 0.05) and a difference between pre-test and post-test scores, indicating that the provision of reproductive health and maternal and child health education had an effect on cadres’ knowledge of reproductive health and MCH in Tugu Subdistrict. With the increase in cadres’ knowledge of reproductive health and MCH, it is expected that they can disseminate this educational information to the community in their respective areas.